A flexible piezoresistive strain sensor based on laser scribed graphene oxide on polydimethylsiloxane - Maham Iqra; Furqan Anwar; Rahim Jan; Mohammad Ali Mohammad (Scientific Reports, 2022)
Abstract Flexible strain sensors are an important constituent in soft robotics, health care devices, and in the defence industry. Strain sensors are characterized by their sensitivity (gauge factor-GF) and sensing range. In flexible strain sensors, simultaneously achieving consistency and high sensitivity has always been challenging. A number of materials and their derivatives have been explored to achieve balanced sensitivity with respect to sensing range with limited results. In this work, a low-cost flexible piezoresistive strain sensor has been developed using reduced graphene oxide (rGO) on polydimethylsiloxane (PDMS). The reduction has been performed using laser scribing, which enables the fabrication of arbitrary structures. After lead-out, the devices were again sandwiched in a layer of PDMS to secure the structures before performing their testing using a locally developed testing rig. Compared to previously reported graphene strain sensors, the devices fabricated in this work show relatively high GF with respect to sensing range. The GF calculated for stretching, bending and torsion was 12.1, 3.5, and 90.3 respectively, for the strain range of 0–140%, 0–130%, and 0–11.1%. A hand test was performed for the detection of joint movement. Change of resistance has been observed indicating muscle motion.